Evaluasi Daftar Pemilih Tambahan Pada Pemilihan Umum Tahun 2024 di Kota Palu - Lahusen, Moh. Rizaldi; Hamid, Abdul; Astuti, Agusta Sri (Program Studi Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2025)
This research is based on problems related to voter transfers that occurred in Palu City during the 2024 General Election. This study aims to evaluate the Additional Voter List (Daftar Pemilih Tambahan, or DPTb) policy implemented during the 2024 General Election in Palu City. The DPTb is a policy regulated under the General Elections Commission Regulation (PKPU) Number 7 of 2022, which seeks to accommodate voters who are unable to exercise their voting rights in their place of origin. This research employs a qualitative approach with a descriptive type and uses Stufflebeam’s CIPP (Context, Input, Process, Product) evaluation model. Data collection techniques include interviews, observation, and documentation. The findings reveal that although the DPTb policy is appropriate for voters who need to vote outside their original constituency and is supported by a strong legal foundation and clear objectives, its implementation in Palu City still faces several challenges. These include a lack of understanding among the public and polling station officers regarding the transfer voting mechanism, as well as weak dissemination of information about the policy. The evaluation of the context aspect shows that the DPTb policy is relevant and beneficial. However, in the input, process, and product aspects, discrepancies in implementation were found, leading to the occurrence of repeat voting (Pemungutan Suara Ulang, PSU) in several polling stations. Therefore, it is necessary to strengthen public outreach, provide technical training, and increase the number of registration posts for transfer voters to ensure the effectiveness of the DPTb policy in future elections.